Effect of Extracts of Pig Spleen and Piglet Skin Cryopreserved Fragments on Blood Leukocyte Profile of Rats with Cold Injury of Skin - Bogatyreva, O. O.; Galchenko, S. Ye.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2024)
The effect of introduction into animals’ peritoneal cavity of the extracts of pigs' spleen and piglets' skin cryopreserved fragments on wound healing rate and blood leukocyte profile of the rats with cold trauma of skin was studied. It has been established that the studied extracts accelerate the healing of skin cold wounds and reveal the manifested immune modulating effect. The findings can be used when developing the immune biological preparations to normalize the process of wound healing.